Intellectual Property Rights and Innovation around the World: Evidence from Panel Data - Andréanne Léger (Deutsches Institut für Wirtschaftsforschung (DIW), 2007)
This article contributes to the literature on innovation and development by identifying the determinants of innovation, and the role of intellectual property rights, in industrialized and developing countries. Controlling for sample selection, I find that, in general, the level of intellectual property protection and a country?s technological capital stock are positively related to research and development investments, while openness to trade has a negative effect. I also find the determinants of innovation to be different for industrialized and developing countries. This is supported by endogeneity tests showing that intellectual property protection is endogenous in industrialized countries, but not in developing countries. However, in both sub-samples, research and development investments Granger-cause intellectual property protection levels, whereas surprisingly, intellectual property protection does not Granger-cause research and development investments.
Keywords: O30; C23; O34; 330; Innovation; intellectual property rights; developing countries; panel data; selection model; Immaterialgüterrechte; Innovation; Forschung; Investition; Industriestaaten; Entwicklungsländer